Penambahan Kuasa Membeli dalam Pembiayaan Murabahah pada Praktik Bank Syariah - Jalaluddin FA (Universitas Batanghari Jambi, 2020)
One of the sharia bank products which is the result of modification is a murabahah financing contract. Namely, buying and selling transactions where the bank mentions amount of profits. The bank as a seller, while the customer as a buyer. In muarabahah, there is a contract known as murabahah with buying authority. The implementation of murababahah with buying authority is, when a customer proposes murabahah financing in Islamic bank, the customer does not only carry out the murabahah financing contract but the customer is also given an authority from the bank to buy the goods desired directly. This study wants to find out whether the implementation of murabahah financing with buying authority allows in Islamic law or not. This research uses normative juridical research type. Researcher analyzes data using descriptive research techniques. This research results that murabahah financing with buying authority is allowed in Islamic law with the condition that in carrying out two contracts is needed to conduct carefully. It must not be conducted in same time, the ownership status must be clarified and the price must be agreed at the beginning of the contract.